The relation between stomata index and drought resistant at rice somaclones of Gajahmungkur, Towuti, and IR 64 - ENDANG GATI LESTARI (Society for Indonesian Biodiversity, 2006)
Plant response to drought stress depends on the physiological and biochemical response of the individual plant. Plant resistant toward the drought stress is controlled by so many genes that identification toward the drought stress resistant plant could use one or several characters related to drought. In order to find out the relationship between stomata density and the drought stress resistant plant, observation on the stomata density at the lower leave epidermis of various rice (Oryza sativa L.) somaclones originated from radiated callus using gamma ray. The observed varieties are Gajahmungkur, Towuti, and IR 64. The plant observed is the ones selected drought resistant by using PEG, root penetration test to paraffin layer, and proline content test. Stomata density observation on several somaclone shows that the radiation treatment to the three varieties may change the stomata width, length and density. Stomata with the lower density than the control shows the higher resistant to the drought viewed from the variable of filled grain, at the stress treatment given in the experiment. Gajahmungkur variety, which is basically higher land rice, has the lower density of stomata than that of Towuti and IR 64. In conclusion, the stomata density can be applied as one indicator on the stress resistant level of rice. Â© 2006 Jurusan Biologi FMIPA UNS SurakartaKey words: stomata, drought resistant, rice (Oryza sativa L.).